The influence of word-of-mouth, perceived ease of use and perceived usefulness on consumer attitudes towards using menstrual cups - Couto, Clara Sá (2020)
Growing appeals for either or both affordable, sustainable and also safe menstrual products have highlighted an enigmatic situation of low acceptance for a product that would meet these exact needs and desires, the menstrual cup. The present analysis illuminates this area by exploring the relation between women’s attitudes towards using this product, and their perceptions of how easy and useful it would really be to use one. Moreover, it is investigated how personal and virtual word-of-mouth might come into play, while taking into account possible mediating effects generated by the same expectations. With this aim in mind, the developed research methodology comprised personal interviews, followed by an online survey, that randomly exposed participants to a stimulus related to either personal or virtual word-of-mouth. Participant’s internal beliefs and attitudes of the two groups were thus recorded and evaluated. Findings suggested that in relation to virtual, personal word-of-mouth can more effectively influence women’s internal beliefs and attitudes towards using a menstrual cup, particularly when targeting perceived ease of use. The contributions made in the present study should be of wide interest to brands planning to implement appropriate marketing strategies with the aim of cultivating positive consumer attitudes towards using menstrual cups and ultimately, encourage acceptance.